La economía social y solidaria como herramienta para fortalecer la formación en emprendimiento con un enfoque rural - Jurado Paz, Irina Margarita; Riascos Mora, Amanda Janneth (SATHIRI, 2020)
The tax culture is related to the way of how taxpayers make as the declaration as the tax payments to the government authority timely, in general terms there is currently no index or procedure to measure properly the tax culture, because it is based on a social perception of how these taxes are established in society. In the present study the tax culture is addressed as close mechanisms that contribute to the methodology of tax collection systems. The main objective of this study is to identify the elements that affect the tax culture of the Association "Sarumaky- Yachay". The study will be conducted through a documentary, descriptive-exploratory analysis, that allows to know the reality of the tax aspects of the sector. The results show that a large number of partners don`t have RUC to carry out their commercial activities (53%), 22% mention that they have RISE, in the same way 22% affirm that they are a taxpayer not obliged to keep accounting and 3% It is registered with RUC as a natural person obliged to keep accounting. Another important result that this research showed is that the main reason why partners cancel their taxes is to avoid fines and penalties with 59%, 25% do so because they consider it to be a civic duty and 13% consider that By not paying taxes you commit a crim.